Challenges and Initiatives in Diversity, Equity and Inclusion in Cancer Molecular Imaging - Daldrup-Link, Heike E.; Esposito, Giuseppe; Bhujwalla, Zaver M. (Frontiers in Oncology, 2021)
Abstract to be confirmed.